Individual Stock Cash Inflow–Outflow Imbalance, Individual Stock Investor Sentiment and Excess Returns. Issue 12 (26th September 2019) - Yang, Chunpeng; Yang, Jianlei
ABSTRACT: Behavioral finance research presents evidence of the importance of "anomaly factors" in the stock market. In this article, we develop an individual stock cash inflow–outflow imbalance index based on individual stock cash inflow and cash outflow and further examine the combined effects of individual stock cash inflow–outflow imbalance and individual stock investor sentiment on excess returns. Our results show that the combined effect of individual stock cash inflow–outflow imbalance and individual stock investor sentiment on excess returns is stronger positive relation. Furthermore, we find that increasing individual stock cash inflow will increase excess returns; on the contrary, increasing individual stock cash outflow will decrease excess returns. Overall, our results highlight the importance of individual stock cash inflow, cash out flow, and cash inflow–outflow imbalance on asset pricing.